Strategi Manajemen Data dan Knowledge Management dalam Meningkatkan Efektivitas Organisasi: Studi Kualitatif Pada Instansi Pemerintah di Kota Padang - Barmitoni Barmitoni; Jhon Veri (Journal of Innovative and Creativity, 2025)
This study aims to review the literature and bring up the implementation of data management and knowledge management strategies in supporting data-based decision making Materials and methods. Data collection techniques were conducted through in-depth interviews with key informants, such as structural officials, data management staff, and staff involved in the information management and decision-making process.. Results. The main obstacles include low digital literacy, limited infrastructure, and the absence of formal policies. However, employees show a positive perception of the importance of data and knowledge, but are not supported by an adequate system. This study recommends the development of a cloud-based information system, data literacy training, and formal policies for sharing knowledge and strengthening a knowledge-based culture. Conclusions. These results provide importance for the digitalization strategy of the public sector bureaucracy